Perceptions of online academics’ and Al-Jazeera.net’s news coverage of the Egyptian political transformation 2013-2014 - Elareshi, Mokhtar; Alsridi, Hatem; Ziani, Abdul-Karim (Penerbit Universiti Kebangsaan Malaysia, 2020)
The growth and expansion of the Internet has enabled many people to communicate and engage in different manners and it is easier than ever now to obtain news and information content via different online sittings. However, concerns grow about the effects of misinformation that has been circulated via different online media sites to influence public views. This research was aimed at exploring online academic news users’ behaviour and their attitudes towards news information given by Al-Jazeera.net during the Egyptian transformation (2013-2014) in Egypt. Based on an online survey (450 users) and focusgroup interviews (six respondents) with Egyptian academics, the research discussed whether users were aware of the media interest or agenda and how users became informed about the political conflict and the transformation, their perceptions of news sites and their evaluation of information regarding this period. The research confirmed that every media has its own interest or agenda when delivering news content, which might favour one side over another. Users indicated that misinformation was found in different forms and, although others underlined the importance of freely accessing online content, there was concern about the spread of misinformation the morality and credibility of online news.